(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Marine insurance is one of the most important sections of insurance, as it provides protection for goods shipped by sea, air, land or railways. Occur because of the risks, which were agreed upon in the marine insurance policy. The research aims to demonstrate the impact of the cost of marine insurance on the profitability of insurance companies and to present the basic concepts of cost, marine insurance and profitability and the importance of this portfolio in the insurance sector, thus identifying the most important criteria that can be applied to measure it within the government research sample companies (National Insurance Company and the Iraqi Insurance Company) and Al-Hamra Insurance Company and Al-Hamra Insurance Company Dar Al Salam Insurance). The problem of the research lies in the weak demand for marine insurance in Iraq and thus affects the cost of marine insurance and the profitability of insurance companies. As for the research method, the descriptive analytical approach was used for the purpose of encompassing all the essential aspects and statistical methods were used (arithmetic mean, standard deviation, coefficient of variation and testing the correlation between The dependent variable (the company’s profitability) and the independent variable (the cost of marine insurance) and the impact test using the statistical program (SPSS23) to extract the cost of marine insurance for each company for the period from (2011-2020) and using the profitability represented by the net profit of the portfolio. The data was collected through the field experience of the researcher in the sample companies search.